Effects of educational intervention on intention to practice planned home birth among midwives in Sokoto, Northern Nigeria - Muhammed, Auwalu (2019)
Background: In Nigeria, two-thirds of women give birth at home by traditional birth attendants and relatives. Home births attended by traditional attendants or family member relate with increased maternal and newborn death. Planned home birth has been empirically found to be safe for low-risk women, but, its practice among midwives is rarely examined in Nigeria. Unless midwives are enlightened about planned home birth, unplanned home births may continue to increase in Nigeria. Education programmes attempted to influence planned home birth practice in other contexts. However, randomised control trials are rarely used to evaluate the planned home birth educational programme. The aim of this study was to develop, implement and determine the effect of educational intervention on the midwives’ intention to practice planned home. Methods: This study used a parallel group randomised control trial to answer the research questions. The target participants were midwives working in the maternity units of the health facilities in Sokoto, Nigeria. A sample of 226 midwives (calculated using a power of 80% at 95% confidence interval, α = 0.05, and attrition of 30% were recruited at random from the health facilities. The study used a reliable and validated questionnaire based on the construct of the theory of planned behavior for data collection. The data collection involves a series of steps: formal entry to the organisation, selection of participants, baseline survey, and assignment of participants to intervention and control groups using stratified block randomisation. The intervention group received planned home birth education. At the end of the educational session, an immediate data collection occurred in both groups. In a month and halve, the intervention group received a phone call to check for understanding of the module. Both groups also received a reminder for the final data collection. At three months after the intervention, data were collected for the third time (three -months follow-up). The control group maintained the usual care during the study. However, at the end of the data collection, the control group received similar planned home birth education classes. The data collection took about six and half months. Finally, data were managed and analysed using descriptive statistics, chi-square test, independent t-test, and linear mixed effects model to evaluate the effect of the intervention. The analysis involved adjusting for the baseline covariates. Results: At the baseline, the results of independent t-test showed a similar (no difference) low to moderate levels of the midwives' attitude, norm, perceived control, knowledge, and intention to practice planned home birth (p>0.05). The test of fixed effect, using linear mixed effect model showed significant main effects of the planned home birth education, time, and their interaction on the midwives’ intention, attitude, norm, perceived behavioural control, and knowledge of planned home birth (p<0.001). The univariate test of within-group effects showed a significant positive change in the level of intention, attitude, norm, perceived behavioural control, and knowledge of planned home birth in the intervention group (p <0.001). However, midwives in the control group had no significant change in the level of the study outcomes (p-values >0.05). An adjusted between-group comparison after the intervention suggested that the planned home birth education group had a stronger level of intention to practice planned home birth (p<0.001) compared with the control group. Moreover, the midwives in the intervention group had a more positive attitude (p <0.001), and positive norm (p<0.001) compared to the midwives in the control group. Similarly, midwives in the planned home birth intervention group had a greater positive behavioural control of planned home birth (p <0.001) compared to the control group after the intervention. Finally, the knowledge of planned home birth after the intervention was found to be higher among the midwives who received planned home birth education (p <0.001) compared to the midwives in the control group. The findings may contribute to the midwifery model of care, and complement the health care stakeholders’ effort for the integration of planned home birth in the conventional maternity system. Conclusion: Planned home birth multi-strategy education is effective in informing and improving midwives’ positive attitude and norm, perceived behavioural control, knowledge, and intention to practice planned home birth for low-risk women. Health system administrators, policymakers, and the researchers may use these strategies to engage midwives in skilled birth attendance at home.